Geospatial Data Curation Steps - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Digital curation can be defined as maintaining and adding value to a trusted body of digital information for current and future use (Beagrie 2006). It is beyond archiving and preservation. Digital data curation is concerned with data management “for as long as it continues to be of scholarly, scientific, research and/or administrative interest, with the aim of supporting reproducibility of results, reuse of and adding value to that data, managing it from its point of creation until it is determined not to be useful, and ensuring its long-term accessibility and preservation, authenticity and integrity” (DCC n.d. in Sandifer n.d.).